Synthesis and Crystal Structure of 3D-Superamolecular Zinc Complex Derived from Pyridine-2,5-dicarboxylate and Oxalate - Yang, Ting-Hai; Han, Yin-Feng; Shi, Fa-Nian (Asian Journal of Chemistry, 2013)
A novel complex, Zn2(Hpdc)2(Ox)(H2O)4] (H2pdc = pyridine-2,5-dicarboxylic acid, Ox = oxalate), has been hydrothermally synthesized and characterized by the elemental analyses, IR spectrum and single crystal X-ray diffraction. Crystal structure analysis reveals that the compound crystallizes in monoclinic space group P2(1)/n, features an interesting 3D-supramolecular network via hydrogen bonding and p-p stacking interactions. Cell unit parameter for the compound: a = 10.2152(3) Å, b = 9.6535(3) Å, c = 10.3594(2) Å, b = 105.664º, V = 983.63(5) Å3, Z = 2, Mr = 623.05, Dc = 2.104 g/cm3, μ = 2.536 mm-1, F(000) = 628, T = 150(2) K, R = 0.0356, wR = 0.0612 for 2510 reflections with I > 2s(I).